The Role of Dynamic Wetting Behavior during Bubble Growth and Departure from a Solid Surface. (June 2021) - Allred, Taylor P.; Weibel, Justin A.; Garimella, Suresh V.
Highlights: Adiabatic bubble growth and departure simulations are performed considering the dynamic wetting characteristics of the surface The receding contact angle is shown to be the dominant wetting characteristic governing maximum contact diameter and departure diameter The advancing contact angle governs the departure mechanism and has a modest influence on the departure diameter Correlations are established for the maximum contact diameter and departure diameter based on the advancing and receding contact angles Boiling surface wetting classifications of hygrophilic, hygrophobic and ambiphilic are defined based on characteristic bubble dynamics ABSTRACT: Surface wettability is known to have a major influence on the ebullition characteristics of a bubble growing from a solid surface. Yet, simplistic static characterization of the wetting behavior is still relied upon to indicate performance characteristics during boiling. In this study, a theoretical framework is developed for the wetting and dewetting processes occurring during bubble growth based upon the dynamic contact angles. This framework is incorporated into adiabatic volume-of-fluid simulations to capture the influence of the surface wettability on contact line and contact angle dynamics during bubble growth and departure. The simulations span a large range of dynamic wetting behaviors and fluid properties. The receding contact angle is shown to govern the early stages of bubble growth as the contact line recedes outward from the bubble center and is the dominant wetting characteristic that determines the maximum contact diameter and departure size. The advancing contact angle dictates the departure morphology as the contact line retracts inward and has a secondary role in determining the departure size. Following, improved reduced-order models are developed that establish fluid-property-independent correlations for the maximum contact diameter and departure diameter as a function of the dynamic contact angles. The results call for the need to redefine wettability classifications based on dynamic contact angles rather than static contact angle in the context of boiling. Hygrophilicity and hygrophobicity are redefined in this context, and an additional classification, ambiphilicity, is introduced for boiling surfaces exhibiting low receding contact angles and high advancing contact angles. Graphical Abstract: Image, graphical abstract